Age‐related characteristics of cutaneous melanoma in a Spanish Mediterranean population. (13th March 2015) - Montero, Iria; Requena, Celia; Traves, Victor; García‐Casado, Zaida; Kumar, Rajiv; Nagore, Eduardo
Abstract Background Melanoma is considered a heterogeneous tumor with genetic and environmental factors involved in its pathogenesis. The impact of these factors varies depending on age. Objective The aim of this study was to characterize the epidemiological, phenotypic, and histological features of patients with melanoma according to three age groups: ≤40, 41–65, and >65 years. Methods A total of 1122 consecutive patients with invasive melanoma definitively treated in our institution since January 2000 were selected from our melanoma database. Epidemiological, phenotypic, and histological data were retrieved and analyzed as a function of age. Results Female patients predominated in the younger age group. The location of cutaneous malignant melanoma differed with age. In the younger and middle age groups, tumors presented mainly on the trunk, while in the older group they were mainly found on the head/neck. Signs of actinic damage such as actinic keratoses, solar lentigines, or other skin tumors increased with age, while genetic factors such as family history of melanoma or a high number of common melanocytic nevi were more frequent in the younger group. Conclusion Our results suggest that melanoma development in younger patients is the result of genetic factors, particularly related to multiple nevi, whereas in older patients environmental factors such as severe chronic sun exposure play a major role.